Microstructural Changes in Normal-Appearing White Matter in Pediatric X-Linked Adrenoleukodystrophy: A Diffusion Tensor Imaging Study - Cebeci, Hakan; Rykken, Jeffrey; Ott, Frederick; Folkertsma, Mark; Koksel, Yasemin; Gencturk, Mehmet (Journal of Pediatric Neurology, 2023)
Objective Diffusion tensor imaging (DTI) is an advanced magnetic resonance imaging (MRI) technique that provides quantitative diffusion data of water molecules in tissue. Usage of DTI in pediatric X-linked adrenoleukodystrophy (X-ALD) may adjunct earlier detection of brain involvement. This study aimed to analyze the normal-appearing white matter in pediatric patients with X-ALD using DTI.Materials and Methods A retrospective database search was performed. Children with genetically diagnosed X-ALDs with a reportedly normal brain MRI between January 2010 and September 2021 were included. Fractional anisotropy (FA), radial diffusivity (RD), axial diffusivity (AD), and apparent diffusion coefficient were serially measured in 8 regions of the brain, and these measurements were compared with those in control patients.Results The study group included 21 X-ALD patients and 11 control patients. The mean age was 6.64 ± 5.14 years. FA values of the genu and body of the corpus callosum were significantly lower in the ALD group than controls. There was also a statistically significant difference in FA, AD, and RD values of cerebellar white matter in the two groups.Conclusion There is evidence of white matter damage on DTI in X-ALD patients with the normal-appearing white matter on conventional MRI sequences. The inclusion of DTI in routine MRI examinations of X-ALD patients may provide additional insight into possible white matter damage in that population.
Keywords: X-linked adrenoleukodystrophy; brain; diffusion tensor imaging; magnetic resonance